Genotoxicity and Micronucleus Formation as a Result of Panoramic Radiography in Epithelial Cells of the Buccal Mucosa: A Cross‐sectional Study in Adults - Nakisa Torabinia; Mojdeh Mehdizadeh; Forooz Keshani; Mohammadreza Mehdizadeh; Parisa Soltani; Gianrico Spagnuolo (Clinical and Experimental Dental Research, 2024)
ABSTRACT Objectives To determine the genetic effects of panoramic radiography on the epithelial cells of the buccal mucosa by examining the micronucleus formation in these cells. Materials and Methods In this cross‐sectional study, exfoliative cytology samples were prepared from the buccal mucosa of 36 patients immediately before and 10 days after panoramic radiography. The samples were prepared using liquid‐based cytology with Papanicolaou staining. The slides were simultaneously evaluated by two expert pathologists and the ratio of the number of cells with micronuclei to the total number of cells on the slide was reported as a percentage. Data analysis was done using paired‐samples T test, Pearson's correlation coefficient, and covariance analysis (α = 0.05). Results The study sample consisted of 24 (66.67%) males and 12 females (33.33%) with a mean (SD) age of 27.36 (8.19) years. The frequency of cells with micronucleus before and after panoramic radiography was not statistically different (p = 0.468). Additionally, the frequency of micronucleated cells was not correlated with age (p = 0.737) and sex (p = 0.211). Conclusion Panoramic exposure slightly increased the frequency of cells with micronucleus in epithelial cells of the buccal mucosa. However, this increase was not statistically significant.